The Complex Role of Aluminium Contamination in Nickel‐Rich Layered Oxide Cathodes for Lithium‐Ion Batteries. Issue 12 (13th July 2021) - Lee, Juhan; Amari, Houari; Bahri, Mounib; Shen, Zonghao; Xu, Chao; Ruff, Zachary; Grey, Clare P.; Ersen, Ovidiu; Aguadero, Ainara; Browning, Nigel D.; Mehdi, B. Layla
Abstract: A major challenge for lithium‐ion batteries based on nickel‐rich layered oxide cathodes is capacity fading. While chemo‐mechanical degradation and/or structural transformation are widely considered responsible for degradation, a comprehensive understanding of this process is still not complete. For the stable performance of these cathode materials, aluminium (Al) plays a crucial role, not only as a current collector but also as substitutional element for the transition metals in the cathodes and a protective oxide coating (as Al2 O3 ). However, excess Al can be detrimental due to both its redox inactive nature in the cathode and the insulating nature of Al2 O3 . In this work, we report an analysis of the Al content in two different types of nickel‐rich manganese cobalt oxide cathode materials after battery cycling. Our results indicate a significant thickening of Al‐containing phases on the surface of the NMC811 electrode. Similar results are observed from commercial batteries (a mixture of NMC532 and LiMn2 O4 ) that were analysed before use and at the end of life, where Al‐containing phases were found to increase significantly at surfaces and grain boundaries. Considering the detrimental effects of the excess Al in the nickel‐rich cathodes, our observation of increased Al content via battery cycling is believed to bring a new perspective to the ongoing discussions regarding the capacity fading phenomenon of nickel‐rich layered oxide materials as part of their complex degradation mechanisms. Abstract : The role of Al : We report that the level of aluminium contamination on nickel‐rich manganese cobalt oxide increases as a function of battery cycles; in particular, the Al‐containing phases were observed at surfaces and grain boundaries. This observation of increased Al content can bring new insights into the ongoing discussions concerning the capacity fading phenomenon of nickel‐rich layered oxide materials in lithium‐ion batteries.